Renegotiating Singapore identity post SG50 - Kang, Janelle Xiaoting (2017)
Singapore identity has been a hot topic with the Singapore government for its criticality in deepening patriotism. To gear up the sense of nationhood, 2015 could be seen as a significant year for Singapore with several high-profile national events from the year-long Golden Jubilee celebrations, passing of its first Prime Minister Lee Kuan Yew, to the General Elections. However, their deeper social impact and influence on national identity has not been studied. Through autobiographical recollection, this study sought to determine the extent to which these events featured in the personal memories of Singaporeans a year onward. Using a timeline-mapping approach, 50 respondents of a relatively young and highly-educated profile plotted their most memorable events in 2015, and six of them were further interviewed. The findings saw a low recollection of public-political memories amid a multitude of personal-domestic memories, despite Mr Lee’s passing was the most remembered national event. This paper offers that Singaporeans value memories related to their personal lives more than public events. Contrary to scholarly review, higher recall of collective memories did not translate to a heightened sense of national identity. Rather, this study found that Singaporeans have different albeit more conditional appreciations of patriotism, and usually based it on long-term factors such as shared culture, relationships, and personal conviction rather than grand-scale national events. These findings provide insights for government policy-makers on what might contribute to national identity.